Questioning the promise of interdisciplinarity: an ethnography of an interdisciplinary research project - Lewis, Ashley (2022)
Interdisciplinarity has been portrayed as the research approach of choice by funders in Europe and the UK. As it is lauded as the necessary research configuration to reach ‘holistic’ solutions to complex problems such as sustainability, researchers and institutions organise their projects accordingly. Interdisciplinarity has become a research topic in itself. However, existing research has principally focused on the reasons why interdisciplinarity research is needed and the challenges to doing it successfully. The popularity of this research approach, coupled with the continued challenges of ‘doing’ interdisciplinarity, suggests that more research is needed to investigate the experiences of the researchers themselves. This research investigates interdisciplinarity in practice by conducting an ethnographic study of academics from both the natural and social sciences at a UK university charged with studying urban sustainability. The research is based on thematic and interpretive analysis and theories from Science and Technology Studies. The data collected between 2016 and 2019 drew from field notes, participant observation, semi-structured interviews, self-recorded diaries and document analysis. The findings from this research suggest that despite the motivation to work in an interdisciplinary way, the lack of a unified definition or incentive to do interdisciplinary work prevented researchers from viewing interdisciplinarity as a primary, integrated objective. In addition, due to the lack of evaluation measures, it was difficult to measure a successful interdisciplinary collaboration; therefore, expectations to meet an interdisciplinary ‘goal’ were unmet. This thesis argues that practising interdisciplinarity within an academic environment makes it difficult to create the incentives necessary to pursue interdisciplinary collaborations and that, in embracing conflict and experimentation, an appreciation for the practice of interdisciplinarity rather than a focus on the outcomes can be achieved.